Pemodelan program holistik dalam intervensi anak stunting lost contact: studi operasional berbasis komunitas - Arfan Syahroni; Tyas Febriana; Mario Sandro; Lienda Wati (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2025)
Abstract Background: Stunting remains a major health problem in Indonesia. Although the prevalence of stunting in Indonesia has decreased from 37.2% to 21.6% in 2022, this figure still exceeds the WHO threshold of 20%. One major challenge in implementing programs is the number of children who are not reached by nutritional interventions, known as